Legal Paradigms in Addressing Social Polarization on Social Media - Yusup, Aldian (Penerbit Mandalika Indonesia, 2024)
This research aims to explore the legal paradigm in overcoming social polarization that is increasingly sharp on social media. This polarization is exacerbated by digital platform algorithms that reinforce